Indoleacetate decarboxylase is a glycyl radical enzyme catalysing the formation of malodorant skatole - Dazhi Liu (Nature Portfolio, 2018)
Skatole is a bacterial metabolite responsible for boar taint and the objectionable smell of manure. Here, the authors elucidate the final step of skatole biosynthesis, describing the discovery and biochemical characterization of the enzyme catalysing the conversion of indoleacetate into skatole.